Cultural retaliation: the cultural policies of the 'new' Front National. Issue 3 (16th April 2019) - Almeida, Dimitri
Abstract: This study examines the conception of culture and the cultural policies of the French Front National. Tracing the developments of the party's cultural agenda before and after Marine Le Pen took over the leadership of the party from her father, I show how the Front National has adapted its discourse on cultural policy to its wider programmatic profile. In the context of a strategy of de-radicalisation promoted by Marine Le Pen, recent years have witnessed focussed efforts by the party leadership to professionalise and modernise the party's cultural policy programme. However, the analysis of the party's current cultural policy agenda reveals a remarkable continuity in the way the party leadership conceives of national culture and of what cultural policy should promote. This programmatic continuity becomes apparent in the analysis of the local cultural policies of municipalities won by the Front National in 2014. Exploring the cultural agendas of ten local governments with a Front National majority, I argue that the cultural policies of the Front National remain deeply rooted in a nativist understanding of culture and a dirigiste approach that wilfully excludes postcolonial minorities.